Monitoring therapy with antibodies - Hale, Geoffrey (Henry Stewart Talks, 2007)
Important things to monitor in clinical trials, Pharmacokinetics, Pharmacodynamics, Unwanted immunogenicity, Regulatory guidance, Good laboratory practice, Good clinical practice, Assay validation, Campath(R) (alemtuzumab), Measuring monoclonal antibodies in blood, Quantitation of minimal disease, Assay formats, Antibodies provide both drugs and the means to monitor them
Reviewed at 2017/11/14